Table of Content - -, (Journal of Economic, Administrative and Legal Sciences, 2023)
Table of Content:1. The quality of accounting information in light of the impact of the use of cloud computing An exploratory study of the opinions of a sample of academics and professionals in IraqTeacher \ Ahmed Hssein Machi , Teacher \ Murtadha Saleh Mahdi , Asst-Teacher \ Ali Noori Abdulzahr2. The impact of the quality of health services on the loyalty of health insurance clients in the state of Jazeera-SudanDr. Amani Abdelatti Omer Alsheekh, Dr. Muhsin Mohammed Gasmalla Ali3. Assessing the application of International Accounting Standards for small and medium-sized Enterprises in OmanDr. Ashraf Abdullateef Abdulrahman Mukhtar4. The impact of strategic planning on knowledge sharing in the Salah Al-Din Health Department in Iraq from the point of view of administrative leaders 2022Asst-Teacher. Anas Khleel Mahdi1 , Co-Prof. Elfadil Timan Idriss1 , Co-Prof. Malikelneem Muhammad Ali15. The Role of The Joint Audit in Reducing the audit expectations gap - A field studyCo-Prof. Bashir Bakri Agib Babiker6. The role of custom in controlling discretionary exchange issues in contemporary financial transactionsDr. Abed Alrahem Ahmed Alsahhar7. Turkey and the chances of membership in the European Union and the future of the relationship 1950-2015Dr. Mohammad Mahmoud Tabtab , Dr. Wesal Abdullah Mohammed Saleh8. Foreign Direct Investment and its Impact on Value Added in the Industrial Sector of the Kingdom of Saudi ArabiaDr. Vivian Mohammed Saleh Nasrulddin , Dr. Sahar Hassan Khayat , Mrs. Maha Ahmed Alharbi9. The Supervisory Role of Labor Inspection in the Control of Labor ViolationsMrs. Alotaibi Mead Mohammed10. The Effect of Organizational Climate on Organizational Commitment in 2022: Case Study - Gaza Electricity Distribution CorporationMr. Wasim M. H. Swidan , Dr. Kalsom Binti Ali , Dr. Ali Nasser Al-Tahitah
Keywords: Journal of Economic, Administrative and Legal Sciences